Adrenal insufficiency induced by immune checkpoint inhibitors anticancer therapy - Paulina Ramaneckaite; Zuzanna Ratuszna; Julia Brymora; Ewa Zalewska; Renata Stodulska-Świątkowska (Nowotwory)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment and significantly improved the prognosisof patients with advanced tumors. The ICIs are monoclonal antibodies that inhibit regulatory proteins, namely cytotoxicT-lymphocyte-associated antigen 4 (CTLA-4), programmed cell death 1 (PD-1), and its ligand (PD-L1). The blockageof the key regulatory signaling pathways allows cytotoxic T lymphocytes to reestablish an effective anticancer response.Despite significant clinical benefits, ICIs may electively provoke toxicity of the endocrine system, including adrenalinsufficiency. Recognizing drug-induced adrenal cortex insufficiency may be challenging due to miser manifestationsand non-specific clinical signs. Therefore, diagnosing adrenal dysfunction requires careful monitoring of cortisol and adrenocorticotropichormone levels during ICIs therapy. This review presents up-to-date research on ICIs-induced adrenalinsufficiency. Studies have shown that early detection of deviations from the norm increases the chances of survivalof ICI-triggered autoimmune adrenalitis, the rare but potentially life-threatening complication of anticancer therapies.